FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN PETUGAS DALAM MENGHADAPI BAHAYA KEBAKARAN (Studi pada Instalasi Pemeliharaan Sarana Rumah Sakit di Rumah Sakit Umum Daerah Kota Salatiga) - Qirana, Muhammad Qifran; Lestantyo, Daru; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (Undip), 2018)
Preparedness is part of the developing disaster management process, the importance of preparedness efforts is one of the most important elements of proactive disaster risk prevention. Hospital buildings are at risk of fire, the use of electrical equipment, short-circuit, pressurized gas cylinders and chemicals can cause a fire. Hospital Facilities Maintenance is one of  Installation that has high risk of fire because it is in charge of facilities maintenance and repairment such as electrical maintenance, repairment of electronic equipment and incelerator. This study aims to analyze factors related to fire emergency preparedness of the Installations of Hospital Facilities and Infrastructure Maintenance (IPSRS) at Salatiga Public Hospital. It was quantitative research with cross-sectional approach. This study involved all IPSRS officers. Data collected by questionnaires and observation checklists as supporting data of fire protection facilities. Based on result of research by using chi-square test, the related variables were knowledge (p-value = 0,011), attitude (p-value = 0,011) and supervision of SHE officer (p-value = 0,002). While unrelated variables were age (p-value = 0,329), gender (p-value = 1,000), work period (p-value = 1,000), education level (p-value = 0,700) and fire protection facility (p-value = 0,089). Researcher suggests employer to complete the fire protection facilities and socialize them to all officers.